Screening Drone Warfare - Delphine Letort (Revue LISA)
While war films contribute to the construction of collective memory, few of them address the changes implied by drone warfare. Drone operators work from remote places and share only one space: the screen that conveys drone images. The possibilities for dramatic actions are too few for a spectacular mise-en-scene: Eye in the Sky (Gavin Hood, 2016) and The Good Kill (Andrew Niccol, 2014) slow down the pace of the narrative to focus on the drones’ power of surveillance. The duration of observation sequences creates spaces for reflection and ethical debates about the military strategy of drone strikes. Such reflection pervades National Bird (Sonya Kennebeck, 2016) and Drone (Tonje Hessen Schei, 2014), two documentaries built from the testimonies of drone operators. This article explores the questions posed in theses fiction and non-fiction films through referring to growing drone literature developed in response to the political arguments in favor of drone warfare.